Cauliflower Growing Technology - Pirimqulova Muxabbat Xayitovna; Mamarajabov Samandarbek Faxriddinovich (Zien Journals, 2022)
This article describes the technology of growing cauliflower, the technologies used from its planting to harvesting.
Keywords: Brassica oleracea convar; botrytis; Alef; superphosphate